2021
DOI: 10.3390/molecules26072054
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Estimation of Cinnamaldehyde and Eugenol in Essential Oils and Traditional and Ultrasound-Assisted Extracts of Different Species of Cinnamon Using a Sustainable/Green HPTLC Technique

Abstract: A wide range of analytical techniques are reported for the determination of cinnamaldehyde (CCHO) and eugenol (EOH) in plant extracts and herbal formulations either alone or in combination. Nevertheless, sustainable/green analytical techniques for the estimation of CCHO and EOH either alone or in combination are scarce in the literature. Accordingly, the present research was carried out to establish a rapid, highly sensitive, and sustainable high-performance thin-layer chromatography (HPTLC) technique for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…C. cassia bark EO has reported similar IC 50 to other authors in other varieties of Cinnamomum bark EOs, such as C. altissium (IC 50 : 0.04 mg/mL) [ 24 ] and C. griffithii (IC 50 : 0.07 mg/mL) [ 20 ], and lower than others (IC 50 : 0.10 mg/mL) [ 20 , 23 ], although in all cases the major compounds are different. It is remarkable that they did not name the compound cinnamaldehyde, which is the major compound reported by several studies [ 25 ], and it is in concordance with this work in which it has been found in an amount of 91.9%.…”
Section: Resultssupporting
confidence: 89%
“…C. cassia bark EO has reported similar IC 50 to other authors in other varieties of Cinnamomum bark EOs, such as C. altissium (IC 50 : 0.04 mg/mL) [ 24 ] and C. griffithii (IC 50 : 0.07 mg/mL) [ 20 ], and lower than others (IC 50 : 0.10 mg/mL) [ 20 , 23 ], although in all cases the major compounds are different. It is remarkable that they did not name the compound cinnamaldehyde, which is the major compound reported by several studies [ 25 ], and it is in concordance with this work in which it has been found in an amount of 91.9%.…”
Section: Resultssupporting
confidence: 89%
“…Most of the analytical methods reported in the literature were used to estimate eugenol quantity in various extracts of tulsi plant and other types of formulations containing clove oils etc., but not for the tulsi ayurvedic formulations. [3][4][5][6][7][8][9][10][11][12][13][14] The current aim of the work is to develop and validate RP-HPLC method for the estimation of eugenol in selected ayurvedic tulsi formulations as per ICH guidelines. 15…”
Section: Introductionmentioning
confidence: 99%
“…Through the simultaneous qualitative and quantitative analysis, the content of various chemical components and the proportion of each component can be determined, hence realizing the quality control of TCM compounds [ 21 26 ]. However, to the best of our knowledge, the methods for determining components used in previous reports only focused on one or two herbs of the whole preparation of GGJTW [ 1 , 27 29 ]. Fang et al developed a method based on the high-performance capillary electrophoresis (HPCE) method with diode array detection (DAD) for the separation and determination of isoflavonoids in Kudzu root [ 27 ].…”
Section: Introductionmentioning
confidence: 99%